Perceptions of Nontraditional African American Baccalaureate Nursing Students of Their Persistence in or Departure From An Urban Nursing Program - Linda S. Rodebaugh (Adult Education Research Conference, 1999)
The literature reflects that although more people of color are enrolling in higher education, graduation rates remain dismal. The purpose of this naturalistic qualitative inquiry was to determine perceptions of experiences of nontraditional African American nursing students regarding their persistence in or departure from a baccalaureate degree nursing program.